Crypts of Hélène Cixous’s Past - Nathalie Debrauwere-Miller (Studies in 20th & 21st Century Literature, 2009)
Through a reading of Cixous’s Inside (1986), Or: Les lettres de mon père (1997), Reveries of the Wild Woman (2006) and Si Près (2007), this article explores the diverse allegories of “enclosure” in the figure of the crypt containing Cixous’s father. Part of the allegory entails a process of mourning not only for the defunct father but for Algeria as well where he is encrypted. The crypt (father’s cave or tomb) as the place and the process of writing imposes the de-cryption of the secret cavities of Cixous’s texts where she is enclosed, inside the father’s cave, in the cavity of his tuberculous lungs, the imagined site from where she writes. The essay focuses on how, with the passage of time, the rapport with the dead father evolves in Cixous’s work and how the figuration of Algeria linked to the disease and death of the father undergoes transformations. The father is described in great detail in Inside and Or, Les lettres de mon père. However in these two early texts, Cixous invents a majestic father incarnating the Law and phallogocentric power as opposed to his condition of a Jew during the Vichy regime, which banned him from practicing his profession and left him powerless. But Cixous never recurs specifically to either identitarian (Jewish) or political (Vichy and Algeria) values. I assert in this essay that it will not be until her later texts that the father’s tuberculosis becomes a foreshadowing of a Jewish condition in occupied Algeria during the Vichy period.
Keywords: Cixous; Les lettres de mon père; Inside; Reveries of the Wild Woman; Si Près; allegories of enclosure; enclosure; crypt; father; Algeria; cave; tomb; passage of time; time; phallogocentric; Vichy regime; jew; jewish